Morphea and Autoimmunity: HLA behind the scene? - Boutrid, Nada; Rahmoune, Hakim (Kansas Journal of Medicine, 2021)
We read with deep attention the case report recently published about the peculiar association of morphea, celiac disease, dermatitis herpetiformis and dermatomyositis , and we would discuss the particular genetics that lay behind morphea and related autoimmune disorders, with a focus on HLA genes.